Improved Estimation of Maximal Reliability for Unidimensional Multicomponent Measuring Instruments in Repeated Measure Studies. Issue 5 (3rd September 2017) - Raykov, Tenko; Marcoulides, George A.; Gabler, Siegfried
Abstract : In repeated measure studies with unidimensional scales, measurement invariance, and specificity stability over time, the specificity variance in each instrument component can be identified. This article describes for that setting an improved point and interval estimation procedure for the maximal reliability coefficient associated with a given set of homogeneous measures. The method is developed within the framework of latent variable modeling and can also be readily used in longitudinal studies for improved point and interval estimation of individual measure reliability and scale reliability at each assessment occasion. The procedure is based on empirically testable conditions and is illustrated with an example.